Given that the first term is LaTeX: t_1=2t 1 = 2, and the recursive definition is LaTeX: t_{n+1}=3^{\left(t_n\right)}t n + 1 = 3
( t n ), what would be the 2nd term (LaTeX: t_2t 2).
2 answers:
<em>*100% CORRECT ANSWERS</em>
Answer:
the correct answer is 9
Step-by-step explanation:
took the test and it was correct
You might be interested in
Answer:
Formula: V = a^3
a = 2in
Input: V = a^3 = 2^3 = 8
Step-by-step explanation:
673
x 86
------------
4038
+ 53840
------------
57878
Answer:
x=- (square root sign) 10 x=(square root sign) 10
Step-by-step explanation:
Answer:
0, 1, 1/2, 22/7, 12345/67, and so on.
Step-by-step explanation:
i just took the test!
Answer:
Hello
Step-by-step explanation:
I'm very streesed out because I have like 50 million assignments due at 11:59 TODAY.